Country Studies o la República Dominicana para angloparlantes Black, Jan Knippers. The Dominican Republic: Politics and Development in an Unsovereign State. Boston, Allen & Unwin, 1986. 164 p. - Sagás, Ernesto (Universidad Autónoma de Santo Domingo (UASD), 1994)
No precisa de un resumen.